A grounded theory of burnout and success stories in psychology graduate school - Almaawali, Mahmood Salim; Abu Shindi, Yousef; Khalaf, Mustafa Ali; Zhai, Yusen (Journal of Interdisciplinary Studies in Education, 2026)
Literature on burnout and stress among psychology graduate students is predominantly cross-sectional, with limited qualitative analysis exploring these phenomena within psychology education. This constructivist grounded theory study interviewed 11 recent graduates from four distinct psychology sub-fields: counseling, measurement, educational psychology, and learning disabilities. This study explored how graduates mitigated burnout and successfully graduated. Findings yielded a process-oriented theoretical model indicating that academic stress slowly developed into psychological burnout, particularly during thesis stage. Both social support networks and intrinsic motivation were the two primary factors buffering against psychological burnout. Self-care, persistence, and psychological resilience were also significant variables in mitigating burnout. These findings provide implications for graduate education and scholarship.